2008
DOI: 10.1002/jcp.21446
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes chondrogenesis in rat mesenchymal stem cells: A role for AKT and hypoxia‐inducible factor (HIF)‐1α

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells capable of developing along the chondrogenic, osteogenic and adipogenic lineages. As such, they have received interest as a potential cell source for tissue engineering strategies. Cartilage is an avascular tissue and thus resides in a microenvironment with reduced oxygen tension. The aim of this study was to examine the effect of a low oxygen environment on MSC differentiation along the chondrogenic route. In MSCs exposed to chondrogenic growth factors, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
187
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(199 citation statements)
references
References 34 publications
12
187
0
Order By: Relevance
“…HIF-2a is stabilized at a wider range of oxygen tensions, ranging from severe hypoxia (o2% oxygen) to more physiologically relevant tension for tumors (2-5% oxygen), whereas HIF-1a is only stabilized at severe hypoxia condition(o2% oxygen). 17,26,33 In this study, we show that HIF-1a may have an important role in hypoxia-mediated maintenance of GSC partly for its interaction with NICD. Besides, we also found that DLL1, a Notch Delta ligand, highly expresses in U251SC both at mRNA and protein level.…”
Section: Discussionmentioning
confidence: 52%
“…HIF-2a is stabilized at a wider range of oxygen tensions, ranging from severe hypoxia (o2% oxygen) to more physiologically relevant tension for tumors (2-5% oxygen), whereas HIF-1a is only stabilized at severe hypoxia condition(o2% oxygen). 17,26,33 In this study, we show that HIF-1a may have an important role in hypoxia-mediated maintenance of GSC partly for its interaction with NICD. Besides, we also found that DLL1, a Notch Delta ligand, highly expresses in U251SC both at mRNA and protein level.…”
Section: Discussionmentioning
confidence: 52%
“…In particular, chondrogenic differentiation under hypoxic conditions results in enhanced cartilage formation and suppresses hypertrophic differentiation (15). In contrast, chondrogenic differentiation under normoxic conditions yields less cartilage, which has a clear hypertrophic signature (11,18,19). Here, we demonstrate that oxygen tension can, in fact, metabolically program the chondrogenic fate of MSCs into different subtypes of hyaline cartilage.…”
Section: Discussionmentioning
confidence: 69%
“…We have previously used such computational models to provide support for the hypothesis that stem cell fate during fracture healing is governed by the local oxygen concentration and stiffness of the surrounding substrate (Burke and Kelly, 2012;Burke et al, 2013Burke et al, , 2014. This algorithm was developed based on in-vitro observations which demonstrate the fundamental role played by substrate stiffness in regulating MSC lineage commitment (Engler et al, 2006;Huebsch et al, 2010;Young et al, 2013;Park et al, 2011), and by experiments demonstrating that hypoxia inhibits osteogenesis and adipogenesis while promoting chondrogenesis (Kanichai et al, 2008;Cao, 2007;Hankenson et al, 2011;Peiffer et al, 2011;Hirao et al, 2006;Street et al, 2002;Gomillion and Burg, 2006;Hausman and Richardson, 2004). This computational model did not however propose a specific hypothesis for how environmental factors regulate the initiation and progression of chondrocyte hypertrophy and endochondral ossification, which is central to successful secondary fracture healing.…”
Section: Introductionmentioning
confidence: 99%